A Musical Pilgrim's Progress - Kubik, Gerhard (International Library of African Music, 1963)
I am happy that just before leaving Uganda I could make some new recordings of a great Musoga singer, Waiswa Lubogo, who is blind, and whom I brought hitchhiking from the Foundation for the Blind to his parents. (His mother had not seen him for a year.) After having reached his home together, where I was received with great friendliness I started to record in the region. (It is near Kaliro, south of Lake Kyoga). I even made a short study of embaire-xylophone playing; because there were two Embaire-bands in the village. All was very encouraging to me and about Basoga music (particularly for Budongo). I know quite something now. One thing I definitely found about the tuning: it is always pentatonic but in the intervals from day to day or from, week to week not constant. Even the best musicians, who tuned their instruments carefully before starting to play, used a slightly different tuning on different days. The tuning of Waiswas instrument I have recorded three times and it always was a little different. But I am also sure that the Basoga Budongo players (at least all those whom I have recorded in the past three years, and they were quite many from many regions) do not like to tune the octaves completely pure. They love a slightly dissonant effect in the tuning of the octave. I intend to write an article soon about Basoga music and I will then give all the references.
Keywords: Ethnomusicology; Musicology; Africa; Travel; African Music